Vitamin B12 Enhances Nerve Repair and Improves Functional Recovery After Traumatic Brain Injury by Inhibiting ER Stress-Induced Neuron Injury - Wu, Fangfang; Xu, Ke; Liu, Lei; Zhang, Kairui; Xia, Leilei; Zhang, Man; Teng, Chenhuai; Tong, Heyan; He, Yifang; Xue, Yujie; Zhang, Hongyu; Chen, Daqing; et al. (Frontiers in Pharmacology, 2019)
Traumatic brain injury (TBI) is one of the most common causes of neurological damage in young human populations. Vitamin B12 has been reported to promote axon growth of neuronal cells after peripheral nerve injury, which is currently used for the treatment of peripheral nerve damage in the clinical trial. Thus, we hypothesized that TBI can be attenuated by vitaminB12 treatment through its beneficial role on axon regeneration after nerve injury. To confirm it, the biological function of vitaminB12 was characterized using hematoxylin and eosin (H&E) staining, Luxol fast blue (LFB) staining, western blot analysis, and immunohistochemistry staining. The results showed that the neurological functional recovery was improved in the VitaminB12-treated group after TBI, which may be due to downregulation of the endoplasmic reticulum stress-related apoptosis signaling pathway. Moreover, the microtubule stabilization, remyelination and myelin reparation were rescued by vitamin B12, which was consistent with the treatment of 4-phenylbutyric acid (4-PBA), an endoplasmic reticulum stress inhibitor. The study suggests that vitamin B12 may be useful as a novel neuroprotective drug for TBI.